2019
DOI: 10.1186/s12884-019-2661-4
|View full text |Cite
|
Sign up to set email alerts
|

Men’s knowledge and involvement on obstetric danger signs, birth preparedness and complication readiness in Burayu town, Oromia region, Ethiopia

Abstract: BackgroundMen’s involvement in obstetrics care is an important strategy in reducing preventable maternal morbidity and mortality. This is particularly important in developing countries where men often make decision on financial, health and other family issues. Hence, the objective of this study was to assess men’s knowledge and involvement in obstetric danger signs; birth preparedness and complication readiness in Burayu town administration, Oromia, Ethiopia.MethodsA community based cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
3
13
2
1
Order By: Relevance
“…Mean age at marriage of the women was 20.517 ± 3.265 years in this study which is more than the mean age at marriage in a study done Madhya Pradesh by Deoki Nandan which was 17.21±1.925 years (5). Mean age of husbands in this study was 29.5 ± 4.9years but in study carried out in Oromia region Ethiopia by Gize et al was 36.6 ± 7 years (16).…”
Section: Discussioncontrasting
confidence: 60%
“…Mean age at marriage of the women was 20.517 ± 3.265 years in this study which is more than the mean age at marriage in a study done Madhya Pradesh by Deoki Nandan which was 17.21±1.925 years (5). Mean age of husbands in this study was 29.5 ± 4.9years but in study carried out in Oromia region Ethiopia by Gize et al was 36.6 ± 7 years (16).…”
Section: Discussioncontrasting
confidence: 60%
“…Similar findings were reported in a study on the effect of a community intervention on the utilization of maternal health care in South-west Ethiopia, that the most known obstetric danger signs were vaginal bleeding, fever, and headache [ 21 ]. Pregnancy-related vaginal bleeding was the most familiar danger sign recognized by the men in a study conducted in Burayu Town, Ethiopia [ 22 ]. Mullany and colleagues also conducted a study in Nepal and reported that the couples had increased knowledge of danger signs of pregnancy as compared to those in the control group [ 23 ].…”
Section: Discussion Of Study Resultsmentioning
confidence: 99%
“…This safeguards against undesirable health outcomes for women and newborns (22). What men know concerning birth preparedness has substantial influence in their participation in maternity care in a positive direction (12,23), and subsequently in the utilization of maternal health services (23).…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, it is the health workers who deliberately exclude men from getting the necessary information about maternal care (10). Other factors responsible for poor male knowledge include low facility delivery of pregnant women and insufficient public health awareness programs (12). Strategies that can improve male participation in maternal health such as enhancing their knowledge of the subject should be given priority; bearing in mind the significant role of the man in ensuring positive maternal health outcomes (11).…”
Section: Introductionmentioning
confidence: 99%